AB0450 Laboratory tests, neurologic complications and modality of referral in 36 patients affected by temporal arteritis: differences between biopsy proven and not biopsy proven patients. (23rd January 2014) - Girelli, F.; Bernardi, S.; Bendo, E.; d'Agostino, G.; Mastroianni, A.; Guidi, C.; Dubini, A.; Nizzoli, M.
Abstract : Objectives: To compare laboratory and clinical parameters in patients with biopsy proven and not biopsy proven temporal arteritis. To evaluate if the incidence of neurologic complications would be influenced by other clinical factors including the modality of referral to rheumatologist. Methods: We retrospectively examined the clinical records of patients who had been diagnosed with giant cell arteritis in our rheumatology unit from February 2007 to December 2012. We recorded data, procedures for referral, time interval between onset of symptoms and diagnosis, clinical features and comorbidities, laboratory exams. Neurologic complications (visual loss, optic and peripheral nerves paralysis) were examined. Biopsy proven and not biopsy proven cases were compared. For the statistical analysis t-Student and Fisher tests were used. Results: Thirty six patients (F 27, M 9, age 75.6 yrs) affected by temporal arteritis were included; twenty four 66.6%) had positive arterial biopsy. Fourteen patients (38.8%) were referred to us from other Units: Neurology 6 pts, Ophtftalmology 5 pts, Otorinolaryngology 2 pts, Infectious Disease 1 pt; the other 22 patients (61.2%) went from the General Practitioner (GP). The time interval between onset of symptoms and diagnosis was shorter in the group with not biopsy proven diagnosis (4.0 and 5.7 months respectively). Biological markers of inflammation were more increased in biopsy positive patients, with statistic relevance for C-reactive protein (p=0.0002). No significant differences were found regarding the presence of polymyalgia rheumatica (p=1), temporal/jaw pain (p=0.37), fever (p=0.48), complications (p=0.47). In the biopsy proven group, complications were more frequent in the presence of arterial hypertension (p=0.31), polymyalgia rheumatica (p=0.25) and when diagnosis was later (p=0.11). Rate of complications was higher in patients from ophthalmologist and otorinolaryngologist (100%) than patients from neurologist (50%), GP (13.6%) and infectivologist (none). Among complicated patients, biopsy was performed less frequently in patients referred to us from ophthalmologist (60%), than from neurologist and GP (66.6%). Among uncomplicated patients, however, the majority of biopsies was performed in those sent from GP (86.3%) compared with those sent from neurologist (66.6%). Conclusions: In our study, C-reactive protein was the only laboratory test significantly higher in the group of biopsy proven patients. No significant clinical correlations have been found between the two groups regarding to polymyalgia rheumatica, temporal/jaw pain or fever. In biopsy proven patients, late diagnosis seemed to be more predictive of complications than arterial hypertension and polymyalgia rheumatica, but the difference is not significant. Patients referred to rheumatologist by other specialists (mostly ophthalmologists) had the higher rate of complications. Disclosure of Interest: None Declared